Efektivitas Rebusan Daun Sirih Merah (Piper Crocatum) Terhadap Penurunan Kadar Gula Darah Penderita Diabetes Mellitus - Sri Mindayani; Wardhah Susanti; Neli Agustin; Jawar Tina (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2019)
Diabetes mellitus is a metabolic disease that arises in a person due to an increase in blood glucose levels above normal values. WHO Data (2016) showed the case of diabetes in Indonesia has an increased tendency of 5.7% in 2007 to 6.9% in 2016. This Data also showed that diabetes with complications is the third highest cause of death in Indonesia. Referring to national prevalency, the Province of West Sumatra has total Diabetes Mellitus as much as 1.3% which is in the order of 14 of the 33 provinces in Indonesia. Incidence of diabetes mellitus disease in Padang City is in the sixth order with the amount of 22,523 cases (DKK Padang, 2017). This research aims to determine the effectiveness of the decoction of red betel leaf to decrease blood sugar levels of people with diabetes mellitus. The research design used was Quasy Experimentwith pretests and posttest group. This research conducted in the area of Puskesmas Padang Pasir from April to August 2019. Sampling techniques was purposive sampling with 10 research subjects, 5 people with 100 ml decoction of betel leaf and 5 people are given a 125 ml decoction of betel leaf for three times daily. The results of the average value before and after the intervention of blood sugar levels can be seen a decrease in blood sugar levels of respondents at a dose of 125 ml. In addition, the time of intervention should be more than 7 days for the effectiveness.